A key to the genera and subgenera of stingless bees in Indonesia (Hymenoptera: Apidae) - Engel, Michael S.; Kahono, Sih; Peggie, Djunijanti (Treubia, 2025)
Indonesia harbors the greatest diversity of social bees in all of Asia, particularly of the stingless bees (Apidae: Apinae: Meliponini). Presently, 46 species of stingless bees are known across Indonesia although records are not comprehensive and additional diversity is likely present across the region. All of the known Asiatic genera of Meliponini occur in Indonesia, making this region a critical center of modern stingless bee biodiversity in Asia. Presented here is an illustrated key to the genera and subgenera of Indonesian stingless bees, as an aid to the general identification, study, and conservation of these critical pollinators.